Prophylactic vacuum sealing drainage (VSD) in the prevention of postoperative surgical site infections in pediatric patients with contaminated laparotomy incisions. Issue 13 (March 2017) - Chen, Bailin; Hao, Fabao; Yang, Yang; Shang, Qingjuan; Guo, Chunbao
Abstract : Abstract: Surgical site infection (SSI) continues to be an issue in abdominal surgery, especially for contaminated (class III) and dirty-infected (class IV) wounds. Vacuum sealing drainage (VSD) was reported effective in the management of various types of wounds or skin grafts. Our goal was to investigate the efficacy of prophylactic VSD to better orient their medicosurgical care of high-risk incisions following laparotomy in a pediatric population. A total of 331 pediatric patients with contaminated (class III) and dirty-infected (class IV) wounds following emergency laparotomy were retrospectively reviewed between January 2005 and January 2013. Among them, 111 cases were placed with prophylactic VSD when incisions were closed. Clinical outcomes, including, overall surgical site complication, device effectiveness, and mean postoperative LOS were evaluated based on VSD usage or not. VSD was applied for an average of 5.8 days (range, 5–7 days), with 3 to 15 mL sucked fluid. The overall SSIs rate was 3% for patients with prophylactic VSD and 17% for patients with convention dressing (OR, 0.27; 95% CI, 0.10–0.71, P  = 0.004). In patients with prophylactic VSD, only 1 of 96 wound developed postoperative incision dehiscence, which is significant reduced compared with patients for conventional dressings (OR, 0.12; 95% CI, 0.01–0.95; P  = 0.017) (Table 2). It also exhibited a decreased mean postoperative LOS ( P  < 0.001) for prophylactic VSD over conventional dressings. Our study demonstrated beneficial postoperative clinical effects of prophylactic VSD for high-risk laparotomy incisions following emergency laparotomy, such as shorter length of hospitalization, which may be attributed to the reduced overall SSIs rate.